The Effect of Internal Control System Implementation and Compensation Suitability on Fraud Prevention with Inspectorate Examination as an Intervening Variable - Set Asmapane; Dwi Risma Deviyanti; Mega Norsita; Dwi Wulandari (Journal of World Science, 2024)
The importance of implementing an internal control system and the appropriateness of compensation in preventing fraud in hospitals. In the health sector, especially hospitals, fraudulent practices such as asset embezzlement, corruption, and fraudulent financial statements often occur, which are detrimental to the state and society. This study aims to analyze and prove the effect of the implementation of the internal control system and the suitability of compensation on the prevention of fraud by inspectorate examination as an intervening variable at the Eye Hospital of the Regional Public Service Agency of East Kalimantan Province. The research method used is quantitative with primary data sources. The sample of this study is 60 employees of the East Kalimantan Provincial Eye Hospital. Data is collected through questionnaires distributed using Google Forms. The data analysis technique used is the Partial Least Squares-Structural Equation Model (PLS-SEM). The results showed that the implementation of the internal control system and inspectorate inspection had a positive and significant effect on fraud prevention, while the appropriateness of compensation had no effect on fraud prevention. In addition, the implementation of the internal control system has a significant effect on the prevention of fraud through the inspectorate's inspection, while the appropriateness of compensation has no effect on the prevention of fraud through the inspectorate's inspection. The implications of this study show that hospitals need to strengthen the internal control system and improve the inspection function of the inspectorate to reduce the risk of fraud.